Privatização da água: de bem comum à mercadoria - Polk, Diorgenes Octávio Nogueira (Universidade Federal de São Carlos, 2025)
This paper aims to recover the historical process of privatization of water and sanitation services in Brazil and some emblematic cases in the international context and their consequences, emphasizing the movements of renationalization that highlight the limits of the privatization model in guaranteeing the human right to water. The historical analysis of the privatization of water and sanitation services, both in the international and Brazilian context, reveals a consistent and deeply worrying pattern: the transformation of a fundamental human right into a commodity and financial asset systematically results in the aggravation of social inequalities, environmental deterioration, and the compromise of universal access.
Privatization of water: from common good to commodity
Keywords: Privatização da água; Políticas públicas; Saneamento básico; Privatization of water; Sanitation services; Public politicies; CIENCIAS AGRARIAS; 6. Água Potável e Saneamento